Conflict transformation and collaboration in developing social forestry in Flores, Indonesia - Prudensius Maring (Forestry Faculty, Universitas Hasanuddin, 2022)
Social movements to realize forest tenure reforms have been ongoing since the 1970s, particularly through policies under the broad umbrella of social forestry. In Indonesia, social forestry programs are initiated by the government, communities, NGOs, academics, companies, and donors, and are based on specific socio-economic and ecological interests. Weak synergies, however between programmatic implementation and stakeholder interests, triggers various forest tenure conflicts. The research examines the complexity of these conflicts, namely focusing around the approaches to conflict transformation that can lead to collaboration in realizing forest sustainability that also support interests of people living in and around forests. I employed a qualitative approach by collecting data through in-depth interviews and participatory observations in Flores in 2017 and 2020. The results show that forest tenure conflicts have occurred since the 1970s due to state forest territorialization. Conflicts culminated in the determination of state forest area boundaries through the 1984 state program entitled the “consensus-based forest land use planning” initiative. Until 2008, efforts to resolve conflicts by offering the community access rights through community forestry programs initiated by the government were rejected by NGOs and the local community. NGOs facilitated communities to demand the return of state forest land as customary forest. This conflict presented the opportunity to facilitate multi-stakeholder forestry programs through a conflict transformation approach by building long-term stakeholder collaboration. Since 2010, the collaboration between stakeholders took place through the community forest program. This study shows the need for more direct attention to studying conflict resolution under an integrated and long-term approach to conflict transformation and collaboration. Pragmatically, this study shows the importance of integrated social forestry policies that synergize various schemes initiated by stakeholders to realize forest sustainability and support local community interests.